Pengaruh Waktu dan Tegangan Listrik terhadap Kadar COD dan Fosfat pada Limbah Cair Nata De Coco Dengan Metode Hibridisasi Pipe Filter Layer-Elektrolisis (HPFLE) - Diky Ihsan Pratama; Ryan Bima Aditya; Siti Fatimah (Universitas Khairun, 2020)
This research is conducting to determine effect of HPFLE (Hibridisasi Pipe Filter Layer-Elektrolisis) method on the waste produced by nata de coco because the waste hs not been too much of a concern of the industrial owner, so that it pollutes the water ecosystem. In this research used two independent variables that is variations in absorbance in the pipe filter layer and variations in voltage and treatment time for the electrolysis stage. Absorbants used in the form of kelaa coir, zeolite, sand, cloth, and sponges. The voltage variations used are 5 volts, 10 volts, and 15 volts while the time variations are 10 minutes, 30 minutes, 45 minutes, 60 minutes, and 75 minutes. From the existing variables, it is known that at the pipe filter layer stage the content of COD gives an effect of 13, 14% while for 9.7% of phosphate. For electrolysis voltage at the COD level which has the best effectiveness at 5 volts with 75 minutes treatment time. As for phosphate, the effective stress is at 5 volts within 10 minutes. From this research, it’s known that HPFLE method gives effect to COD level to 4000 mg/L while for phosphate to 179,01 mg/L.